The Changing Face and Focus of the Adolescent with an Eating Disorder - Chason, Carly; M. Davis, Krista; J. Hanks, Lynae; Casazza, Krista (Journal of Nutritional Therapeutics, 2016)
The classic silhouette of the typical adolescent with an eating disorder (ED) is a white female with extremely low body weight; this has begun to take a new shape. The most apparent shift in the classic views are sex and weight. A trend toward a progressively decreasing age of onset in ED has also emerged. The objective of this paper is to describe the ED patients presenting to Children’s of Alabama’s Adolescent Eating Disorders Clinic, encompassing their age, sex, BMI percentile and muscle function. The data was examined from all first presentations to the clinic from 2013 to 2016. Between May 2013 and March 2016, 102 new patient appointments were scheduled. 88 patient’s charts were reviewed from the time of each initial appointment in the Adolescent Eating Disorders Clinic to obtain the sex, age, race, height, weight, reason for referral/active problems and ED diagnosis for each patient. BMI percentile was calculated according to reference ranges for sex and age. Handgrip strength was measured by dynamometer. As is consistent with previously published data, there were significantly more females than males seen in our population. There were more females than males across all categories of ED diagnoses. The highest number of diagnoses occurred between the ages of 13-16. A positive correlation between BMI percentile and measured handgrip strength was observed. Measured handgrip strength in females was lower in ages 13-18 than expected grip strength for age. When males were grouped by “Males 14 and under” and “Males 15 and over,” a lower measured grip strength compared to the expected grip strength for age was demonstrated. The impact of ED on morbidity and mortality has been well recognized; however the most often reported association was mainly based on changes in body weight. The adverse metabolic consequences perturb nutrient sensing and ultimately delivery and utilization. A shift in the focus of energy balanced towards systemic malnourishment may allow healthy and sustained metabolic improvements.